Commercial Map of the World - Hinman, Russell, 1853-1912; Bradley & Poates (American Book Company, 1890)
This sheet includes multiple maps; on the front is a commercial map of the world. The commercial map is color-coded to show different aspects of commerce (the key is in the lower right corner) and also uses red and black lines to mark trade and communication routes as well as ocean currents (the key is in the lower left corner). Additionally, red text marks the locations of products and industries across the world. Bodies of water and geographic features are marked (with relief shown by hachures). On the back of the commercial map, there are multiple other maps on two pages. The page on the left has a central political map of the world labeled "The World To-Day" and is surrounded by maps showing portions of the world from different time periods. On the right half, there are four maps: a small inset of "Ancient Rome" in the upper left corner, "Italy at the time of Augustus" in the upper right corner, "Greece at the time of Pericles" in the middle of the page and to the left, and "Palestine, Lower Egypt and part of Arabia, A.D. 70" at the bottom. All of the maps use colored shading to mark different regions or features.